Hydrogeochemical effects of hydropower regulation on river-aquifer continuum in boreal rivers - Siergieiev, Dmytro (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2014)
Hydropower infrastructure affects many large rivers worldwide, threatening riverine and coastal ecosystems by fragmenting flow, disturbing landscapes and water retention and altering sedimentation and primary production. This thesis investigated major impacts of hydropower regulation on hydrological and geochemical processes in large boreal rivers. Geochemical river transport, sediment composition and hydrogeochemical functioning of the river-aquifer interface were studied in the regulated Lule River and the unregulated, otherwise similar, Kalix River in Northern Sweden.Regulation halved mean maximum runoff and tripled minimum runoff and winter transport of total organic carbon (TOC), Fe, Si, suspended Mn and P compared with the unregulated river. Summer suspended C/N ratio was 10-20 and <10 in the regulated and unregulated river, respectively, indicating organic matter decay during long residence times in Lule River reservoirs. Suspended P/Fe ratio varied little annually in the regulated river, indicating low abundance of phytoplankton. Sediment cores from the headwater reservoir revealed simultaneous Fe and P sequestration under a Mn-oxyhydroxide layer on the sediment surface. Reservoirs also enhanced diatom production and sedimentation of non-detrital Si, decreasing Si transport to the sea. Retention of total Fe, Si and P was 15%, 7% and 25% of the total river transport, respectively.The river-aquifer interface (hyporheic zone) functioned differently in the two rivers. Daily oscillating discharge in the regulated river and reduced spring peaks caused riverbed colmation, impairing river-aquifer exchange and forming stagnant subsurface areas. The hyporheic zone functioned as a source/sink of Fe, Mn, dissolved OC and NH4 in the regulated/unregulated river. Regulation also altered temporal hydraulic gradients dynamics between river and aquifer favouring solute pulses and presumably causing irregular TOC patterns at the river mouth.Hydrological modelling of river-aquifer interactions indicated that short-term ...